High-strength temperature-stable composite dielectric material as well as preparation method and application thereof

By combining ceramic modified polymer resin with a prefabricated body of a high-performance fiber braided structure, the problem that existing microwave dielectric materials are difficult to achieve low dielectric constant and high mechanical strength in the fields of high frequency and high speed communications is solved, and composite dielectric materials with high strength, low dielectric constant and low loss are realized, which are suitable for a variety of microwave equipment.

CN119704720AActive Publication Date: 2025-03-28SHAOXING UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510223142.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-28
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

It is difficult for existing microwave dielectric materials to achieve low dielectric constant, near zero resonance frequency temperature coefficient, high mechanical strength and good processing performance at the same time in the fields of high frequency and high speed communications.

Method used

The prefabricated body using a tiled stacked fabric structure, a three-dimensional orthogonal structure or a three-dimensional angular interlocking structure is compounded with a ceramic modified polymer resin solution, and the dielectric performance is regulated through ceramic particles, and the mechanical performance is improved by combining high-performance fibers with resins.

Benefits of technology

A composite dielectric material with high strength, low dielectric constant and low loss is achieved, with a resonance frequency temperature coefficient close to zero, and the overall performance of the material is significantly improved. It is suitable for filters, resonators and microwave dielectric substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a high-strength temperature-stable composite dielectric material as well as a preparation method and application thereof. The preparation method of the composite dielectric material comprises the following steps: carrying out composite molding on a preform formed by weaving fibers and a ceramic modified resin mixed solution to obtain the high-strength temperature-stable composite dielectric material, wherein the structure of the prefabricated body is a tiled stacked fabric structure, a three-dimensional orthogonal structure or a three-dimensional angle interlocking structure. The fiber, the ceramic and the polymer are subjected to composite forming, meanwhile, the excellent mechanical property of the fiber reinforced composite material and the excellent dielectric property of the ceramic material are combined, and the resonant frequency temperature coefficient of the composite material is regulated and controlled, so that the high-strength and temperature-stable composite dielectric material is obtained, and the composite dielectric material has the advantages of low dielectric constant and high temperature stability. Meanwhile, the composite material has excellent mechanical property and stable dielectric property, can be used as a substrate material of microwave devices such as resonators, antennas, filters and the like, and is widely applied to the industries of military industry, national defense, transportation and power electronics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microwave dielectric materials, and in particular to a high-strength, temperature-stable composite dielectric material and a preparation method and application thereof. Background Art

[0002] With the rapid development of communication technology, microwave dielectric materials are increasingly used in fields such as filters, resonators and microwave substrates, which puts higher requirements on the performance of microwave dielectric materials. Especially in the field of high-frequency and high-speed communications, microwave dielectric materials need to have both low dielectric constant ( ) to increase the signal transmission rate, and the resonant frequency temperature coefficient close to zero ( ) to ensure the stability of the device frequency. However, while achieving a low dielectric constant and a near-zero resonant frequency temperature coefficient, it is also necessary to take into account the mechanical strength and processing performance of the material, which poses a great challenge to material design and preparation technology.

[0003] At present, traditional microwave dielectric materials mainly use ceramic materials, which are widely used in the preparation of resonators and substrates due to their excellent dielectric properties and high-temperature stability. However, ceramic materials often have a high dielectric constant, which is not conducive to high-speed signal transmission. In addition, their high brittleness, low dielectric breakdown strength, and harsh processing conditions limit their extensive application and adaptability. Low dielectric constant polymer-based composites have broad application prospects in wireless communication systems. By combining microwave dielectric ceramics with low dielectric constant polymers, the dielectric properties of the composites can be regulated to a certain extent. So far, a significant increase in the resonant frequency temperature coefficient of polymer composites can only be obtained under high ceramic loads, which results in high dielectric constants and low mechanical properties of polymer composites. To achieve high-strength, low dielectric constant and low-loss polymer composites, solving the problem of poor mechanical properties and dielectric properties has always been a long-term challenge. Therefore, a new process is needed to prepare high-performance composite dielectric materials with high strength, low dielectric constant, and resonant frequency temperature coefficient close to zero. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a high-strength, temperature-stable composite dielectric material and a preparation method and application thereof. A preform having a flat stacked fabric structure, a three-dimensional orthogonal structure or a three-dimensional angular interlocking structure is composited with a ceramic-filled modified polymer resin solution. Ceramic particles are used to regulate the dielectric properties of the composite material to ensure a low dielectric constant and a resonant frequency temperature coefficient. The high-performance fiber and resin composite ensure the mechanical properties of the material, thereby solving the problems raised in the above-mentioned background technology.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: According to a first aspect of the present invention, a method for preparing a high-strength and temperature-stable composite dielectric material is provided, wherein a preform formed by weaving fibers is composite-molded with a ceramic-modified resin mixed solution to obtain the high-strength and temperature-stable composite dielectric material; wherein the structure of the preform is a flat-stacked fabric structure, a three-dimensional orthogonal structure, or a three-dimensional angle interlocking structure.

[0006] The present application is to compositely form fibers, ceramics and polymers, and at the same time combine the excellent mechanical properties of fiber-reinforced composite materials with the excellent dielectric properties of ceramic materials, thereby obtaining a high-strength and temperature-stable composite dielectric material. The flat stacking structure, three-dimensional orthogonal structure or three-dimensional angle interlocking structure fabric is used as a reinforcement in the composite material, which greatly enhances the mechanical properties of the material along the fiber direction. The polymer resin wraps and fixes the fiber, so that the load between different fibers is transferred through the resin, optimizing the load transfer path, thereby further improving the overall strength of the material. In addition, this combination method effectively prevents the agglomeration of ceramic particles, and can ensure the uniformity and stability of the dielectric properties of the composite dielectric material. Ceramic particles have a large resonant frequency temperature coefficient. Ceramic particles are added to the resin matrix of the fiber-reinforced composite material, so that the composite material has the intrinsic dielectric response of ceramics, thereby regulating the stability of the dielectric properties of the composite material, and finally preparing a high-strength and temperature-stable composite dielectric material.

[0007] Preferably, the ceramic material is selected from at least one of strontium titanate, barium titanate and calcium titanate.

[0008] Preferably, the polymer resin is selected from thermosetting resins or thermoplastic resins.

[0009] Preferably, the polymer resin is selected from at least one of epoxy resin, polyimide resin, phenolic resin, polytetrafluoroethylene resin, vinyl resin and polypropylene resin.

[0010] Preferably, in the mixed solution containing ceramic material and resin, the ceramic material accounts for 20-30wt% of the mixed solution.

[0011] Preferably, the fiber of the preform is selected from at least one of glass fiber, aramid fiber, polyethylene fiber, basalt fiber, polyphenylene sulfide fiber and polytetrafluoroethylene fiber.

[0012] Preferably, the composite molding process is selected from any one of hand lay-up molding, injection molding, resin transfer molding, vacuum assisted resin transfer molding, hot pressing molding, and autoclave molding.

[0013] According to a second aspect of the present invention, there is provided a high-strength and temperature-stable composite dielectric material obtained according to the above-mentioned preparation method, wherein the resonant frequency temperature coefficient of the composite dielectric material is -30ppm / °C to +30°Cppm / °C; The tensile strength of the composite medium material is 400-1100 MPa.

[0014] Preferably, the dielectric constant of the composite dielectric material is 3.85-4.5, and the dielectric loss is ≤0.02.

[0015] According to a third aspect of the present invention, there is provided an application of a high-strength and temperature-stable composite dielectric material in filters, resonators and microwave dielectric substrates.

[0016] The present invention provides a high-strength, temperature-stable composite dielectric material and a preparation method and application thereof, which have the following beneficial effects: (1) This scheme provides a method for preparing a high-strength and temperature-stable composite dielectric material, which combines a preform fiber with a ceramic-resin mixed solution, and optimizes the mechanical properties and dielectric properties of the material by utilizing a flat stacked fabric structure, a three-dimensional woven orthogonal structure, or a three-dimensional angle interlocking structure. This not only significantly improves the strength and impact resistance of the composite material, but also reduces the dielectric constant, achieves a resonant frequency temperature coefficient close to zero stability, and improves the thermal stability and processing performance of the material.

[0017] (2) This scheme provides a high-strength and temperature-stable composite dielectric material that can simultaneously meet the requirements of high strength, low dielectric constant, low dielectric loss, and near-zero resonant frequency temperature coefficient, which can improve the performance of filters, resonators, and microwave dielectric substrates. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] The present invention provides a method for preparing a high-strength and temperature-stable composite dielectric material, wherein a ceramic material is uniformly mixed into a polymer resin through high-speed mechanical stirring to obtain a mixed solution, and a preform woven from fibers and the mixed solution containing the ceramic material and the resin are composite-molded to obtain the high-strength and temperature-stable composite dielectric material; wherein the structure of the preform is a flat-stacked fabric structure, a three-dimensional orthogonal structure, or a three-dimensional angle interlocking structure.

[0020] In a specific embodiment, the ceramic material is selected from at least one of strontium titanate, barium titanate, and calcium titanate. Further preferably, the ceramic material is selected from strontium titanate. The present application selects strontium titanate ceramic material with a low dielectric constant and a resonant frequency temperature coefficient close to zero. It can have good dispersibility and bonding with the polymer resin and the fibers of the preform, and can be evenly distributed in the matrix to ensure the structural stability and performance consistency of the composite material. Furthermore, the prepared composite dielectric material combines the characteristics of the preform and the ceramic material, and while improving the strength, it also has toughness and impact resistance.

[0021] In a specific embodiment, the particle size of the ceramic material is 1 to 5 μm. Optionally, the particle size of the ceramic material is selected from any value of 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or a range between any two values. By limiting the particle size of the ceramic material, the ceramic material can be fully in contact with the resin matrix and the reinforcement fiber, thereby improving the interface bonding force, and improving the mechanical properties and stability of the composite material. In addition, the particle size within this range helps to control the packing density and distribution between the ceramic materials, thereby reducing the dielectric constant of the composite dielectric material.

[0022] In a specific embodiment, the polymer resin is selected from a thermosetting resin or a thermoplastic resin. Specifically, the polymer resin is selected from at least one of epoxy resin, polyimide resin, phenolic resin, polytetrafluoroethylene resin, vinyl resin, and polypropylene resin. The polymer resin selected in the present application has a low dielectric constant and dielectric loss, has good insulation properties under high-frequency and high-speed signal transmission environments, and helps to reduce the dielectric constant of the composite dielectric material as a whole.

[0023] In a specific embodiment, in the mixed solution containing ceramic material and resin, the ceramic material accounts for 20-30wt% of the mixed solution. Optionally, the ceramic material accounts for any value of 20wt%, 25wt%, 30wt% of the mixed solution or a range value between any two values. Within the range of 20-30wt%, a good interface bonding can be formed between the ceramic material, the resin matrix and the fibers of the prepolymer. Too much or too little ceramic material will cause interface bonding failure, and the addition of ceramic material within this range can also balance the relationship between dielectric constant and mechanical properties, avoiding the problem of too high dielectric constant and poor clamping functionality due to too high ceramic material.

[0024] In a specific embodiment, the fiber of the prepolymer is selected from at least one of glass fiber, aramid fiber, polyethylene fiber, basalt fiber, polyphenylene sulfide fiber, and polytetrafluoroethylene fiber.

[0025] In a specific embodiment, the composite molding process is selected from any one of hand lay-up molding, injection molding, resin transfer molding, vacuum assisted resin transfer molding, hot pressing molding, and autoclave molding.

[0026] The following will further illustrate a high-strength, temperature-stable composite dielectric material and its preparation method and application in conjunction with specific embodiments of the present invention.

[0027] Example 1 (1) Laying down 6 layers of glass fiber woven mesh cloth with a gram weight of 400 g to obtain a glass fiber laminate structure preform with a thickness of 2 mm; (2) mixing strontium titanate ceramics with a particle size of 1 μm with epoxy resin and a curing agent, and fully stirring them with a high-speed stirrer to obtain a mixed solution in which the strontium titanate ceramics account for 30 wt% of the total content; (3) The mixed solution was filled into the glass fiber laminate structure preform through the VARTM molding process, the vacuum degree was controlled at -0.1 MPa, pre-cured at 50°C for 3 h, and cured at 70°C for 7 h to obtain a laminate structure ceramic filled glass fiber / epoxy resin temperature-stable microwave composite dielectric material.

[0028] Example 2 (1) A 3D orthogonal structural fabric with a thickness of 2 mm was prepared by using 3D weaving technology using 300 tex glass fiber as a preform; (2) mixing strontium titanate ceramics with a particle size of 1 μm with epoxy resin and a curing agent, and fully stirring them with a high-speed stirrer to obtain a mixed solution in which the strontium titanate ceramics account for 30 wt% of the total content; (3) The mixed solution was filled into a three-dimensional orthogonal structure glass fiber preform through the VARTM molding process, the vacuum degree was controlled at -0.1 MPa, pre-cured at 50°C for 3 h, and cured at 70°C for 7 h to obtain a three-dimensional orthogonal structure ceramic filled glass fiber / epoxy resin temperature-stable microwave composite dielectric material.

[0029] Example 3 (1) A 3D angle interlocking structure aramid fabric with a thickness of 2 mm was prepared by 1500 denier aramid fiber through a 3D weaving technology as a preform; (2) mixing barium titanate ceramics with a particle size of 1 μm with epoxy resin, and fully stirring them with a high-speed stirrer to obtain a mixed solution in which the barium titanate ceramics account for 30 wt% of the total content; (3) The mixed solution was filled into a three-dimensional angle interlocking structure aramid fabric preform through the VARTM molding process, the vacuum degree was controlled at -0.1 MPa, pre-cured at 50°C for 3 h and cured at 70°C for 7 h to obtain a three-dimensional orthogonal structure ceramic filled aramid fiber / epoxy resin temperature-stable microwave composite dielectric material.

[0030] Example 4 (1) A 3D orthogonal structure fabric with a thickness of 2 mm was prepared by 3D weaving technology using 1500 denier aramid fiber as the reinforcing aramid fiber; (2) mixing strontium titanate ceramics with a particle size of 1 μm with polyimide resin, and fully stirring them with a high-speed stirrer to obtain a mixed solution in which the strontium titanate ceramics account for 30 wt% of the total content; (3) The mixed solution was evenly coated on the surface of the reinforcing aramid fiber through a hand lay-up process, so that the mixed solution could fully penetrate into the interior of the fabric. The mixed solution was pre-cured at 160°C for 30 minutes, 260°C for 40 minutes, and 310°C for 40 minutes. During the curing process, an imidization reaction occurred to obtain a three-dimensional orthogonal structure ceramic-filled aramid / polyimide composite dielectric material.

[0031] Example 5 The preparation method of this embodiment is the same as that of embodiment 5, except that the strontium titanate ceramic accounts for 20 wt % of the mixed solution.

[0032] Comparative Example 1 30wt% of strontium titanate ceramic, 20wt% of aramid fiber powder and 50wt% of polyimide are fully mixed by a high-speed stirrer to obtain a mixed solution; the mixed solution is placed in a mold, pre-cured at 160°C for 30 minutes, pre-cured at 260°C for 40 minutes, and cured at 310°C for 40 minutes to obtain a composite dielectric material plate.

[0033] Comparative Example 2 The preparation method of this comparative example is the same as that of Example 5, except that the strontium titanate ceramic accounts for 0wt% of the mixed solution.

[0034] Comparative Example 3 The preparation method of this comparative example is the same as that of Example 5, except that the strontium titanate ceramic accounts for 10 wt % of the mixed solution.

[0035] Comparative Example 4 The preparation method of this comparative example is the same as that of Example 5, except that the strontium titanate ceramic accounts for 35wt% of the mixed solution.

[0036] The performance of the composite dielectric materials prepared in Examples 1 to 6 and Comparative Examples 1 to 6 was tested, as shown in Table 1.

[0037] Table 1

[0038] By comparing Examples 1-4 with Comparative Example 1, it can be seen that the traditional method of adding short fibers to ceramic-polymer resin to improve the mechanical properties of ceramic-polymer materials can only achieve a tensile strength of 75MPa for microwave dielectric composite materials, but the effect of short fibers on improving the mechanical properties of composite materials is not significant. In the experimental scheme of this project, a fabric prepared from high-performance fiber long fibers is used as a reinforcement, and then combined with a ceramic-modified polymer resin, which effectively improves the mechanical properties of the composite material compared to the ceramic-polymer-based composite material prepared by the traditional method. In addition, different fiber raw materials and structures can be used to achieve ceramic-modified fiber-reinforced composite materials with different properties. By selecting fibers and resins, the mechanical properties of the composite material can be further improved, while achieving high strength and low resonant frequency temperature coefficient.

[0039] By comparing Examples 4-5 with Comparative Examples 2-4, it can be seen that by filling the ceramic material into the fiber-reinforced composite material, the dielectric properties of the overall composite material can be successfully regulated as a physical modifier. When the strontium titanate ceramic particle filling content is 20wt%~30wt%, a low resonant frequency temperature coefficient ( ), thereby ensuring the stability of the dielectric properties of the composite material at different temperatures. The resonant frequency temperature coefficient of microwave dielectric materials satisfies the mixing law, so the overall resonant frequency temperature coefficient can be adjusted by adding materials with different resonant frequency temperature coefficients. Strontium titanate ceramics (+1100ppm / ℃) have the opposite resonant frequency temperature coefficient to fibers and resins, so they can effectively improve the temperature stability of the overall composite material.

[0040] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-strength and temperature-stable composite dielectric material, characterized in that: The ceramic material is evenly mixed into the polymer resin through high-speed mechanical stirring to obtain a mixed solution, and the preform woven from fibers is composite-molded with the mixed solution containing the ceramic material and the resin to obtain the high-strength and temperature-stable composite dielectric material; wherein the structure of the preform is a flat stacked fabric structure, a three-dimensional orthogonal structure, or a three-dimensional angle interlocking structure.

2. The method for preparing a high-strength and temperature-stable composite dielectric material according to claim 1, characterized in that: The ceramic material is selected from at least one of strontium titanate, barium titanate and calcium titanate.

3. The method for preparing a high-strength and temperature-stable composite dielectric material according to claim 1, characterized in that: The polymer resin is selected from thermosetting resins or thermoplastic resins.

4. The method for preparing a high-strength and temperature-stable composite dielectric material according to claim 3, characterized in that: The polymer resin is selected from at least one of epoxy resin, polyimide resin, phenolic resin, polytetrafluoroethylene resin, vinyl resin and polypropylene resin.

5. The method for preparing a high-strength and temperature-stable composite dielectric material according to claim 1, characterized in that: In the mixed solution containing ceramic material and resin, the ceramic material accounts for 20-30wt% of the mixed solution.

6. The method for preparing a high-strength and temperature-stable composite dielectric material according to claim 1, characterized in that: The fiber of the preform is selected from at least one of glass fiber, aramid fiber, polyethylene fiber, basalt fiber, polyphenylene sulfide fiber and polytetrafluoroethylene fiber.

7. The method for preparing a high-strength and temperature-stable composite dielectric material according to claim 1, characterized in that: The composite molding process is selected from any one of hand lay-up molding, injection molding, resin transfer molding, vacuum assisted resin transfer molding, hot pressing molding, and autoclave molding.

8. A high-strength and temperature-stable composite dielectric material obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The resonant frequency temperature coefficient of the composite dielectric material is -30ppm / °C~+30°Cppm / °C; the tensile strength of the composite dielectric material is 400~1100MPa.

9. A high-strength and temperature-stable composite dielectric material according to claim 8, characterized in that: The dielectric constant of the composite dielectric material is 3.85-4.5, and the dielectric loss is ≤0.

02.

10. Use of the high-strength and temperature-stable composite dielectric material according to claim 8 or 9 in filters, resonators and microwave dielectric substrates.

Citation Information

Patent Citations

  • Method for preparing dielectric regulation fiber reinforced resin-based composite material

    CN116100932A

  • Composite material with adjustable dielectric constant, flexible transmission line dielectric material and electronic equipment

    CN118027601A

  • Reinforcing fiber substrate, composite dielectric substance and method for producing the same

    JP2002212337A

  • Manufacturing method of continuous carbon fiber-reinforced composite materials and manufacturing method of composite formed article

    KR1020180020541A

  • Composite material and high-frequency circuit substrate made therefrom

    US20100258340A1